Evaluation of Long-Term Liabilities at MSME Mooka Kopi and Their Impact on Financial Performance - Wahyuni; Amelia Rezki Septiani Amin; Suci Awaliyah; Suci Ramadhani; Muhammad Akshah Halik; Muh. Alfai (www.amertainstitute.com, 2026)
Micro, Small, and Medium Enterprises (MSMEs) frequently rely on long-term liabilities to finance business expansion; however, inadequate financial literacy and weak debt management often reduce financial performance and increase solvency risk. This community service project aimed to evaluate the management of long-term liabilities at Mooka Kopi MSME in Makassar, Indonesia, and to strengthen the owner's capacity to assess their impact on financial performance through structured accounting practices. The program employed a participatory assistance approach involving field observations, interviews, financial document reviews, debt classification, amortization simulations, journal preparation, and solvency ratio analysis based on the Indonesian Financial Accounting Standards for Private Entities (SAK EP). The evaluation focused on long-term notes payable and mortgage financing used to support business expansion. The findings indicate that systematic debt evaluation improved the accuracy of liability recording and enhanced the owner's understanding of interest allocation, principal repayment, and financial statement preparation. Solvency analysis revealed a Debt-to-Asset Ratio of 41.82%, a Debt-to-Equity Ratio of 71.87%, and a Long-Term Debt-to-Equity Ratio of 60.18%, suggesting that the enterprise maintained a relatively healthy capital structure despite utilizing external financing. Furthermore, the assistance program improved financial decision-making by enabling the business owner to monitor repayment obligations and assess the sustainability of future investments. This initiative demonstrates that practical accounting assistance combined with financial ratio analysis can strengthen financial governance, improve transparency, and enhance the long-term sustainability of MSMEs by promoting informed debt management and evidence-based business decisions.